Estudio de la eficiencia de un filtro sumergido y un filtro percolador en el tratamiento secundario de las aguas residuales domésticas, Moyobamba - Rodriguez Tuesta, Alberth Anthony (2014)
The present investigation raised determine efficiency in removing pollutants from the effluent of a septic tank using a biological filtration system, the system was composed of two units of secondary treatment, a submerged filter and a trickling filter, both with identical characteristics of 1.53 m in height and 0.20 m in diameter. lt was used as packing material, polypropylene rings of % -inch and 2.5 cm in length, placed in both treatment units, forming a height of 1.3 m in the ftlters. For the operation of the submerged filter, and trickling filter system in series, two treatments was performed, with and without artificial injection of air generated by two small air pumps, one for each treatment unit. It was determined that the best removal efficiencies were submerged filter to the 80 days since the start of operation when injected artificial air, concentrations of 16 mg/1 of BOD, 51 mg/1 of COD and 36 mg/1 of TSS, meaning efficiencies of 94 %, 88% and 82% forthe removal ofBOD, COD and TSS respectively. The best removal efficiencies of the trickling filter were at 60 days after the operation start when injected artificial air, concentrations of 58 mg/1 BOD, 93 mg/1 of COD and 68 mg/1 of TSS, meaning efficiencies of 77 %, 77% and 63% for the removal of BOD, COD and TSS respectively. For the system of biological treatment in series, formed by filter plunged more the submerged filter with injection of artificial air obtained efficiencies of 83 %, 95 % and 89 % for the parameters TSS, BOD and COD respectively. The results indicate that both the trickling filter such as the submerged filter units are important for waste water treatment, fulfilling widely with the LMP for waste water treatment plants that establishes the Peruvian legislation.